Clarifying knowledge withholding: A systematic literature review and future research agenda - Gonçalves, Tiago (2023)
Knowledge withholding (KW) is a relatively recent multidimensional construct in the knowledge management literature. A diverse and polymathic series of studies has aimed to understand the conceptual and empirical inconsistencies associated with KW. Based on a systematic literature review, in this paper, we examine and discuss theoretical backgrounds, antecedents, consequents, and methodological choices related to KW research by reviewing papers published between 2000 and 2021. Results show differences between KW-related constructs, namely knowledge hiding and knowledge hoarding, offering an integrative view of the phenomena. Findings clarify differences between KW constructs. This paper also offers insight into future research directions related to KW by elaborating on identified inconsistencies and gaps. Our work contributions include an overview and clarification of the KW research agenda, proposing a comprehensive analytic framework that aims to guide future research and serve practical implications.